Efficiency assessment of public universities in South Africa, 2009-2013: Panel data evidence - Myeki, L.W.; Temoso, O. (South African Journal of Higher Education, 2019)
With ever increasing enrolments of students into the public universities and limited funding, assessing the efficiency of universities is vital for effective allocation and utilisation of educational resources. Are higher education institutions in South Africa making the most efficient use of resources made available to them? This study attempts to provide an answer to this question. We apply a Data Envelopment Analysis (DEA) approach to assess technical efficiency (TE) of 22 public universities in South Africa for the period 2009 to 2013. A university is said to be efficient if it is producing maximum output (number of graduates and publications) from a minimum quantity of inputs (number of staff, students’ enrolments, and expenditure). The results indicates that over the study period the average TE of universities declined from 0.83 to 0.78. Research-intensive universities were more efficient than professional-oriented universities. These results can help key decision makers such as the Commission on Higher Education and universities management in identifying possibilities for improving institutional performance by identifying their strengths and weaknesses and benchmarking with their peers.